2020
DOI: 10.1021/acs.cgd.0c00110
|View full text |Cite
|
Sign up to set email alerts
|

2D-Coordination Polymers Based on Rare-Earth Propionates of Layered Topology Demonstrate Polytypism and Controllable Single-Crystal-to-Single-Crystal Phase Transitions

Abstract: A series of rare-earth propionate based complexes [Ln 2 (H 2 O) 2 Prop 6 ] (Ln = Y, Ho−Lu) were synthesized in the form of two polymorphs (α and β), both being layered 2D-coordination polymers with identical geometries of the single layers. The polymorphs differ from each other in the layer arrangement, and therefore they are considered the first example of polytypes among aliphatic rare-earth carboxylates. Strategies toward the controllable crystallization of each polytype have been developed. The β polytype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
(100 reference statements)
4
10
0
Order By: Relevance
“…According to a recent review, this transformation can be classified as a martensitic transition, which is rare among coordination compounds. These findings complement the incredibly diverse crystallography of coordination polymers along with our recent studies in SCSC transitions found among lanthanide propionate complexes …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…According to a recent review, this transformation can be classified as a martensitic transition, which is rare among coordination compounds. These findings complement the incredibly diverse crystallography of coordination polymers along with our recent studies in SCSC transitions found among lanthanide propionate complexes …”
Section: Resultssupporting
confidence: 82%
“…It is worth noting that metal complexes with organic ligands are capable of exhibiting polymorphism and even polytypism. In particular, flexible groups may undergo superstructural ordering on cooling , that may give rise to functional properties in the corresponding compounds: for instance, ferroelectricity or spin crossover. , Thus, the heterometallic s and d metal (e.g., copper) propionates are of specific interest in this respect as a convenient modeling system. On the one hand, these are expected to be coordination polymers consisting of copper-based SBUs in accordance with the aforementioned strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Figures and show XRPD measurements recorded under heating conditions to confirm the high-temperature phase transformations of the AZM-DH crystals. This diffraction study furnishes qualitative and quantitative information about the structural changes, as well as corroborates the thermodynamic effects observed through the thermal analysis techniques, which the sample undergoes with the temperature variation. …”
Section: Resultssupporting
confidence: 71%
“…An interesting case of polytypism was reported for a family of 2D-polymeric yttrium and heavy lanthanide (Ho–Lu) propionates [Ln 2 (H 2 O) 2 Prop 6 ] ∞ , which proved to adopt two polytypic modifications capable of mutual solid-state transformations . Furthermore, a novel structural type of 2D-polymeric RE propionates has been recently reported by us for lanthanum propionate hydrate [La 2 (H 2 O) 2 Prop 6 ] ∞ , which is not isomorphic to Y and Ho–Lu compounds described earlier.…”
Section: Introductionmentioning
confidence: 99%
“…In general, metal propionate complexes (MProp n L m here, L is an ancillary ligand) are valuable materials due to their unique structural features. Namely, flexible ethyl groups in propionate anions are able to rotate, which leads to unusual lattice dynamics and phase transitions. , Regarding the layered rare-earth propionates, one could expect a highly anisotropic thermal expansion with large positive and negative linear coefficients of thermal expansion (CTEs) that could be useful for the development of high-precision thermal actuators. Indeed, many anisotropic coordination polymers are known to exhibit anomalous (anisotropic or/and negative) thermal expansion; on the other hand, there are reports on colossal negative thermal expansion (NTE) promoted by the rotation or/and reorientation of certain structural units. In particular, a combination of both factors gave rise to NTE for 1D-polymeric rare-earth pivalates where the negative α CTE of −128 MK –1 was reached . Furthermore, in general, CTEs are additionally packing-dependent. , Therefore, the studies of RE propionate polytypes and their thermal expansion represent significant interest.…”
Section: Introductionmentioning
confidence: 99%